2020
DOI: 10.2147/jpr.s275680
|View full text |Cite
|
Sign up to set email alerts
|

<p>Anterior Cervical Surgery for the Treatment of Cervicogenic Headache Caused by Cervical Spondylosis</p>

Abstract: Study Design Retrospective study. Objective To report the efficacy of anterior cervical surgery for the relief of cervicogenic headache (CEH) caused by cervical spondylosis. Methods From January 2014 to December 2016, a total of 166 cases of cervical radiculopathy and/or myelopathy received anterior cervical decompression and fusion (ACDF) in our institution, among which 50 cases (mean age 44.7 years) were accompanied by CEH and followed up a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…This study has also shown that CEH in patients with cervical radiculopathy and/or myelopathy significantly improved or disappeared after ACDF, which was consistent with previous studies ( 6 , 17 , 22 ). To the best of our knowledge, to date, no large-scale, prospective, multicenter study has examined the efficacy of ACDF to relieve CEH diagnosed based on the ICHD-3 beta version.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This study has also shown that CEH in patients with cervical radiculopathy and/or myelopathy significantly improved or disappeared after ACDF, which was consistent with previous studies ( 6 , 17 , 22 ). To the best of our knowledge, to date, no large-scale, prospective, multicenter study has examined the efficacy of ACDF to relieve CEH diagnosed based on the ICHD-3 beta version.…”
Section: Discussionsupporting
confidence: 92%
“…It has long been considered a referred pain caused by pathological changes in the upper cervical nerves (C1–C3) ( 2 ). However, as we all know, cervical spondylosis occurs mostly in the lower cervical spine (C4–C7) and rarely in the upper cervical spine ( 5 , 6 ). In reality, Diener et al ( 7 ) and later Persson et al ( 8 ) identified the role of the lower cervical spine as a potential source of CEHs in the early 21st century.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have also shown that after cervical disc degeneration, in ammatory factors can be released to sensitize surrounding mechanoreceptors and cause dizziness. Previous case reports have shown that some patients with cervical spondylosis may experience relief of headache and dizziness after cervical laminectomy 25 , and cervical dizziness caused by cervical disc herniation can be signi cantly improved after disc replacement 26 .In addition, studies have shown that physical traction therapy can also improve dizziness symptoms in patients with cervical spondylosis 27 , which all suggest that the relief of dizziness symptoms is related to the reduction of cervical disc pressure and pressure around nerve roots. Combined with the results of this study, the dizziness symptoms of most patients are a persistent drowsiness in the head, which may be accompanied by mental depression and poor sleep quality.…”
Section: Discussionmentioning
confidence: 96%